A Systematic Review of Internet of Things (IoT) Applications in Sustainable Project Management in Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Rowter Journal, 2026)
The rapid advancement of Internet of Things (IoT) technologies has created significant opportunities for sustainable project management in developing countries, including Ethiopia. As Ethiopia advances initiatives such as the Digital Ethiopia 2030 strategy, smart city programs, and climate-resilient development policies, IoT integration has become increasingly important in infrastructure, agriculture, energy, and environmental management. This systematic review examines the current applications, benefits, and challenges of IoT in sustainable project management within the Ethiopian context. The study employed a structured review methodology using academic databases, institutional repositories, government publications, and peer-reviewed literature. A total of 23 relevant studies and policy documents were critically analyzed using thematic synthesis approaches to identify sectoral applications, sustainability contributions, and implementation barriers. The findings indicate that IoT applications in Ethiopia are concentrated in construction and infrastructure, agriculture, energy systems, and environmental monitoring. IoT technologies improve economic sustainability through operational efficiency, resource optimization, and reduced maintenance costs. Environmental sustainability benefits include real-time monitoring of ecosystems, efficient resource utilization, and climate resilience. Social sustainability outcomes involve enhanced food security, infrastructure safety, and public service reliability. However, adoption remains constrained by inadequate infrastructure, high implementation costs, limited technical expertise, cybersecurity concerns, and weak institutional coordination. The study concludes that IoT technologies possess substantial potential to support sustainable development in Ethiopia. The review recommends increased investment in digital infrastructure, technical capacity building, localized innovation, and stronger regulatory and cybersecurity frameworks.